BUSINESS ANALYSIS ON Net Cage Floating Fish Caltivation IN PT Thoyyibatul Rizki PLTA Koto Panjang Reservoir - Syahruzal Syahruzal; Hamdi Hamid; Hazmi Arief (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted on April 5, 2017 until April 10, 2017 at PT Thoyyibatul Rizki Koto Panjang Hydroelectric Reservoir Kabupaten Kampar Riau Province. The purpose of this research are: to know the analysis of net cage net cultivation of fish and fish tilapia in PT Thoyyibatul Rizki PLTA Waduk Koto Panjang, To know the total cost of business production keramba net floating fish cultivation Mas and fish Nila PT Thoyyibatul Rizky Reservoir hydropower Koto long , To know the income and the acceptance of the cultivation of floating net cages PT Thoyyibatul Rizky Koto Panjang Hydroelectric Reservoir. The method used in this study is a case study with the purpose according to Nazir (2013), case study is research on the status of research subjects related to a specific phase or typical of the overall personality, the subject of research can be individuals, groups, institutions .             Cultivators obtain Nila and Mas Fish Seed from PT. Popan Solok, feed obtained from PT. Popan, according to the cultivators so far the availability of feed is always fulfilled. For the labor of the cultivators employs 4 people that is from the side of the family and from outsiders, where the ability of this workforce obtained from the direction of the owner of the cultivation and also experience during their cultivation activities. For the access itself is very smooth and there are no obstacles, because the location of the cultivation is very strategic that is close to the highway. Based on the results of research efforts undertaken have been done calculate the value of BCR and FRR So it can be concluded that financially the business of fish cultivation Mas and Nila fish in keramba floating net Koto Panjang hydroelectric dam conducted by fish farmer PT Thoyyibatul Rizky profitable and feasible to be developed again and continued. Net income is the result of a reduction of income with total costs incurred so as to derive income production of goldfish and tilapia. Keywords:Business Analysis,Production,Labor, Operational Cost and Working Capital